Pemanfaatan Teknologi Aplikasi Pengelolaan Keuangan BUM Desa di Desa Malawaken Kecamatan Teweh Baru Kabupaten Barito Utara - Saputra, Ade Chandra; Agus Sehatman Saragih; Deddy Ronaldo (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2023)
This service aims to study and implement innovative and effective financial management applications for Village-Owned Enterprises (VE). Good financial management is key to advancing the village economy and improving community welfare. Involving surveys, interviews and analysis of VE Desa needs related to financial management, this service also involves VE managers and Village Apparatus. The activity plan consists of planning, implementation, socialisation and evaluation. The planning stage included initial discussions with VE managers for application functionality and identification of application components based on needs. As a result, an application was designed that includes transaction recording, data processing, and structured financial report preparation. Training for VE managers on the application and financial management was conducted. VE managers were active in the implementation to ensure compliance. The results show that the application can be used well by VE managers from the data input stage to the output of VE financial reports. It is expected that this application supports the active role of VE in the village economy, creating jobs, and improving community welfare.